Black activity spaces in Shaker Heights. (3rd July 2021) - Grigsby, Alan V.
ABSTRACT: The majority of Americans reside in suburbs and today's suburbs are becoming more racially diverse than ever before. My research uses an ethnographic approach to investigate social life in one racially diverse suburb of Cleveland, Ohio: Shaker Heights. Specifically, I investigate how Black Americans who occupy this space—as residents, employees, and visitors—think about, describe, and participate in social life in a diverse suburb. I conclude that, although Shaker is statistically integrated, the activity spaces and social lives of Black adults do not reflect this demographic reality. The findings from this study will help researchers better understand dynamics of community life and race relations in suburbia; a neighborhood type that is both seldom explored and growing in demographic importance.